Interlayer quantum transport in Dirac semimetal BaGa2 - Sheng Xu (Nature Portfolio, 2020)
The transport behavior at the quantum limit may show exotic phenomena such as special interlayer quantum transport. Here, the authors observe negative interlayer magnetoresistance resulted from tunneling of Dirac fermions between the zeroth Landau levels in BaGa2, indicating a feature at the quantum limit.